A three level solar panel system with an automated solar tracker - Moniruzzaman, H. M.; Patwary, Munia; Rahman, Mosaddequr (© 2014 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the 3rd International Conference on the Developments in Renewable Energy Technology, ICDRET 2014; Dhaka; Bangladesh; 29 May 2014 through 31 May 2014 [© 2014 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICDRET.2014.6861671